The impact of adoption of an electronic health record on emergency physician work: A time motion study - Samantha Calder‐Sprackman; Glenda Clapham; Trisha Kandiah; Jade Choo‐Foo; Simran Aggarwal; Julia Sweet; Khadeer Abdulkarim; Courtney Price; Venkatesh Thiruganasambandamoorthy; Edmund S.H. Kwok (Journal of the American College of Emergency Physicians Open)
Abstract Objective We assessed the impact of the transition from a primarily paper‐based electronic health record (EHR) to a comprehensive EHR on emergency physician work tasks and efficiency in an academic emergency department (ED). Methods We conducted a time motion study of emergency physicians on shift in our ED. Fifteen emergency physicians were directly observed for two 4‐hour sessions prior to EHR implementation, during go live, and then during post‐implementation. Observers performed continuous observation and measured times for the following tasks: chart review, direct patient care, documentation, physical movement, communication, teaching, handover, and other. We compared time spent on tasks during the 3 phases of transition and analyzed mean times for the tasks per patient and per shift using 2‐tailed t test for comparison. Results Physicians saw fewer patients per shift during go‐live (0.51 patient/hour, P < 0.01), patient efficiency increased in post‐implementation but did not recover to baseline (−0.31 patient/hour, P = 0.03). From pre‐implementation to post‐implementation, we observed a trend towards increased physician time spent charting (+54 seconds/patient, P = 0.05) and documenting (+36 seconds/patient, P = 0.36); time spent doing direct patient care trended towards decreasing (−0.43 seconds/patient, P = 0.23). A small percentage of shifts were spent receiving technical support and time spent on teaching activities remained relatively stable during EHR transition. Conclusion A new EHR impacts emergency physician task allocation and several changes are sustained post‐implementation. Physician efficiency decreased and did not recover to baseline. Understanding workflow changes during transition to EHR in the ED is necessary to develop strategies to maintain quality of care.